Strategi Pengembangan Pasar & Inovasi Produk “Idea Corporation” Untuk Menjangkau Pasar Yang Lebih Luas - Bayu Andris Johano; Faruq Lamusa; Niluh Putu Evvy Rosanty (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Central Sulawesi has a large market potential in the manufacturing creative industry. This has encouraged IDEA CORPORATION's business as a creative manufacturing business to work on the needs of the community, both producing decorations/furniture as well as souvenirs. However, in the process there are still many obstacles that will be corrected from the SWOT analysis that will be carried out. The purpose of the SWOT analysis and determination of the Business Model Canvas can certainly be used as a reference for evaluating business models and correcting deficiencies, overcoming threats, and optimizing opportunities as well as taking advantage of strengths. The results achieved from this process are that IDEA CORPORATION's business has made changes both in terms of market development strategy and production innovation, as well as its production system.